1998
DOI: 10.1021/om970829v
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of a Coordinated Acetonitrile Ligand:  Synthesis of an Ethylimido Complex of Tungsten

Abstract: Treatment of the dinitrogen complex W(N2)2(dppe)2 (1; dppe = 1,2-bis(diphenylphosphino)ethane) with trifluoromethanesulfonic acid yields the novel hydrazido complex [W(N2H2)(OTf)(dppe)2]+[OTf]- (2; OTf = CF3SO3 -). The triflato ligand is readily displaced by other ligands and coordinating solvents. The triflato complex 2 yields the complex [W(N2H2)(NCCH3)(dppe)2]2+ (5), when it is dissolved in acetonitrile, and 5 is readily deprotonated by a variety of bases to give the acetonitrile−dinitrogen complex W(N2)(NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 38 publications
3
32
0
1
Order By: Relevance
“…For both compounds, the more shielded methylenic resonance exhibits a large coupling to the bridging fluoride ( 4 J FH = 10−13 Hz) and is significantly broader than the other one. For comparison, 4 J HF = 3.7 Hz for the trans ethylimido fluoro complex [W(F)(NEt)(dppe) 2 ]BF 4 . We interpret the unusual broadening effect as derived from the presence in solution of some H-bonding interaction between this proton and the tetrafluoroborate counterion, as found in the solid state.…”
Section: Resultsmentioning
confidence: 85%
“…For both compounds, the more shielded methylenic resonance exhibits a large coupling to the bridging fluoride ( 4 J FH = 10−13 Hz) and is significantly broader than the other one. For comparison, 4 J HF = 3.7 Hz for the trans ethylimido fluoro complex [W(F)(NEt)(dppe) 2 ]BF 4 . We interpret the unusual broadening effect as derived from the presence in solution of some H-bonding interaction between this proton and the tetrafluoroborate counterion, as found in the solid state.…”
Section: Resultsmentioning
confidence: 85%
“…To confirm that [ 3 (N 2 ) 2 ]BF 4 was protonated only at the metal center, the reaction was performed with a 15 N-labeled amine in the PNP ligand, trans -[W(N 2 ) 2 (dppe)(P Et ( 15 N) Me P Et )][BF 4 ] ( 1 (N 2 ) 2 ( 15 N)). The corresponding 15 N{ 1 H} NMR spectrum of trans -[W(N 2 ) 2 (H)(dppe)(P Et ( 15 N) Me P Et )][BF 4 ] ([ 3 (N 2 ) 2 ( 15 N)]BF 4 ) contains a triplet at δ −362 ( J NP = 14 Hz) and does not exhibit 15 N–H coupling (typically ∼80 Hz) , in the proton-coupled 15 N NMR spectrum. Seven-coordinate transition-metal hydride bis(dinitrogen) complexes have been reported for Mo and W supported by traditional chelating phosphine ligands (such as dppe) upon reaction with mineral acids such as HCl in methanol or THF, , and additional details are described below.…”
Section: Resultsmentioning
confidence: 99%
“…The starting compounds [MCl(NEt)(dppe) 2 ]Cl (1; M = Mo/W) were prepared by reaction of the mixed acetonitrile-N 2 complexes [M(N 2 )(CH 3 CN)(dppe) 2 ] (M = Mo, W) with HCl in benzene (Scheme 1). 7 Under these conditions, the acetonitrile ligands are protonated to yield the corresponding M(IV) ethylimido complexes. 7, 9 Recently we investigated this reaction in more detail and found that in complexes of the type [M(N 2 )(CH 3 CN)(diphos) 2 ] (M = Mo, W; diphos = dppe, depe) the nitrile ligand is activated towards protonation at the sp carbon center after exchange of dinitrogen by a Lewis base X, in general the conjugated base of the acid HX employed for protonation.…”
Section: Resultsmentioning
confidence: 99%